PENGEMBANGAN MEDIA FLIPBOOK UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN DI TK TUNAS TELADAN GANDUS PALEMBANG - Gita Rizkia; Kurnia Dewi; Tutut Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a flipbook-based learning media to improve the cognitive skills of children aged 5-6 years at TK Tunas Teladan Gandus Palembang. This research employed a Research and Development (R&D) approach using the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects included three expert validators (material expert, media expert, and language expert), as well as field test participants consisting of 6 children in the small group trial and 15 children in the large group trial. The validation results showed that the flipbook media obtained an average validity score of 86%, categorized as very valid, with details: media validation 86%, language validation 80%, and material validation classified as very good. Based on the practicality test, the flipbook media was considered highy practical because it is easy to operate, interactive, and engaging for children. Furthermore, the effectiveness test demonstrated that the use of flipbook media successfully improved children’s cognitive abilities, including logical thinking, classifying, differentiating, and understanding cause-and-effect relationships independently and meaningfully. In conclusion, the developed flipbook media is feasible, valid, practical, and effective to be used as a learning tool to enhance the cognitive development of early childhood learners.